Canalization and plasticity in psychopathology. (15th March 2023) - Carhart-Harris, R.L.; Chandaria, S.; Erritzoe, D.E.; Gazzaley, A.; Girn, M.; Kettner, H.; Mediano, P.A.M.; Nutt, D.J.; Rosas, F.E.; Roseman, L.; Timmermann, C.; Weiss, B.; et al.
Abstract: This theoretical article revives a classical bridging construct, canalization, to describe a new model of a general factor of psychopathology. To achieve this, we have distinguished between two types of plasticity, an early one that we call 'TEMP' for 'Temperature or Entropy Mediated Plasticity', and another, we call 'canalization', which is close to Hebbian plasticity. These two forms of plasticity can be most easily distinguished by their relationship to 'precision' or inverse variance; TEMP relates to increased model variance or decreased precision, whereas the opposite is true for canalization. TEMP also subsumes increased learning rate, (Ising) temperature and entropy. Dictionary definitions of 'plasticity' describe it as the property of being easily shaped or molded; TEMP is the better match for this. Importantly, we propose that 'pathological' phenotypes develop via mechanisms of canalization or increased model precision, as a defensive response to adversity and associated distress or dysphoria. Our model states that canalization entrenches in psychopathology, narrowing the phenotypic state-space as the agent develops expertise in their pathology. We suggest that TEMP – combined with gently guiding psychological support – can counter canalization. We address questions of whether and when canalization is adaptive versus maladaptive, furnish our model with references to basic and human neuroscience, and offer concrete experiments and measures to test its main hypotheses and implications. This article is part of the Special Issue on "National Institutes of Health Psilocybin Research Speaker Series". Highlights: The entrenchment of thought or behavior is proposed to be a common factor to psychopathology. This entrenchment is linked to a historical construct called 'canalization'. Canalization is proposed to be a common defensive reaction to adversity. Biological markers of canalization, and its counteraction, are proposed.